Water regulation by grasslands: a global meta‐analysis - Sirimarco, Marina Ximena; Barral, Maria Paula; Villarino, Sebastian; Laterra, Pedro (Wiley Online Library, 2018)
Grasslands have been modified and replaced worldwide and have affected water regulation ecosystem services. In order to support public policies attending to the consequences of different grassland modifications and replacements, general patterns and models about their consequences on water regulation are needed. We quantitatively meta‐analysed the results of 110 site‐specific studies analysing infiltration (83) and evapotranspiration (28) responses to grasslands alterations by grazing, crops, and afforestation and how these responses vary with environmental factors. In grasslands, soil water infiltration is significantly reduced by grazing and cropping on average by 51% and 57%, respectively. Water infiltration is increased by 65% in response to afforestation. The reduction of infiltration with grazing decreases with soil sand content and increases with the mean annual precipitation (PPT) and the ratio PPT/mean annual potential evapotranspiration. The replacement of grasslands by forests increases evapotranspiration by 30%, and the variation of this response was linearly related to PPT and the PPT/mean annual potential evapotranspiration ratio. There was a negative trend in evapotranspiration responses although not significant, when grasslands were replaced by crops or modified by grazing. Our meta‐analysis was able to reveal average patterns and the influence of local climate and soil properties on eco‐hydrological responses to grasslands modifications and replacements, which have not been previously described. These results may support general predictive models on the influence of land use changes and ecosystem services provision. Significant gaps were found in the number of studies, especially of evapotranspiration, precluding the achievement of a general conclusion regarding evapotranspiration and infiltration responses.